Cool Mix Asphalt—Redefining Warm Mix Asphalt with Implementations in Korea, Italy and Vietnam - Hosin (David) Lee; Lan Ngoc Nguyen; Elena Sturlini; Young-ik Kim (Infrastructures)
During the past decades, to minimize Greenhouse Gas (GHG) emissions and asphalt fumes during the asphalt mix production and construction process, various warm mix asphalt (WMA) additives have been developed and successfully applied. Currently, as production of WMA reaches close to that of Hot Mix Asphalt (HMA) in the US, the varied definition of WMA is questioned in this paper. Not only are the temperature reduction ranges from HMA defined by various studies too wide, but also the minimum threshold to be classified as WMA is often too small. In this paper, a new category of “Cool Mix Asphalt (CMA)” is proposed to distinguish it from the newly defined WMA based not on the reduction amount from HMA temperature but its actual production temperature. It is proposed that HMA should be defined as asphalt mixtures produced at temperatures between 140 and 160 °C (between 284 and 320 °F), WMA as production temperatures between 120 and 140 °C (between 248 and 284 °F), and CMA as production temperatures between 100 and 120 °C (212 to 248 °F). By defining their actual production temperatures rather than reduction temperatures from HMA, WMA and CMA will be clearly defined. This paper then presents a new Polymer Cool Mix Asphalt (PCMA) additive called “Zero-M”, which was developed to lower the mixing temperature to around 110 °C (203 °F). Recently, test sections using Zero-M were successfully constructed in Korea, Italy and Vietnam, and their laboratory test results of field cores and production and construction experiences are described in this paper. The chemistry and compositions of Zero-M are discussed along with its mechanism to significantly lower the production temperature of PCMA. All test sections constructed in three countries met the in-place compaction density requirements of their respective countries, which were close to or higher than those of the control HMA test sections.